(untitled) (International Current Pharmaceutical Journal, 2014)
Antibiotics are generally prescribed for both as prophylactically (before orthopaedics surgery etc.) or to treat ongoing infection (like septic arthritis, osteomyelitis etc.) in the orthopaedics department. But if antibiotics are not use rationally then there will be increase chances of resistance of bacteria as also as deteriorate the patients disease condition which ultimately increase the total cost of treatment. The goal of this study was to see the antibiotics utilization pattern. A prospective cross-sectional, multicentre drug utilization study was conducted for a period of 3 months to evaluate the pattern of antibiotics use in orthopaedic unit of various hospitals of Dhaka City, Bangladesh. A total of 498 prescriptions were studied; in which 160 prescriptions contained mono-antibiotic therapy (51.79%) and 147 prescriptions contained poly-antibiotics therapy (48.21%) and the beta-lactam antibiotics were most commonly prescribed (81.68%). Mono-antibiotics prescriptions were the common pattern than combination and brand name has been prescribed frequently than generic. To minimize cost, it is advisable to promote prescription of generic drugs. Also justifying efforts are needed to improve appropriateness of antimicrobial therapy and minimize the development of antimicrobial resistance. Hence the results of the study showed that there is a considerable scope for improvement in the prescription pattern. DOI: http://dx.doi.org/10.3329/icpj.v3i9.19896 International Current Pharmaceutical Journal, August 2014, 3(9): 318-321